Bone healing patterns in osteoporotic patients: study on titanium surfaces treated with Vitamin D nanoparticles - Francesco Gianfreda; Michele Miranda; Gabriele Ambrogio; Joseph Cannillo; Maria Scarpati Cioffari di Castiglione; Patrizio Bollero; Marco Gargari; Mirko Martelli (Annali di Stomatologia)
Introduction: Dental implantology has emerged as a vital solution for edentulism, effectively restoring masticatory function and improving patients’ quality of life. Despite advancements, osseointegration remains critical for the success of implants, particularly in osteoporotic patients where bone quality is compromised. This study explores the enhancement of osseointegration through titanium surfaces treated with vitamin D nanoparticles. Materials and Methods: Grade 4 titanium discs were treated using sandblasting and acid etching (SLA) to improve surface roughness. The discs were then immersed in a vitamin D nanoparticle solution produced via nanoemulsion. The biological effectiveness was assessed through cellular viability tests (MTT), bone mineralization assays (Alizarin Red staining), and quantitative PCR for osteogenic marker expression. To measure cell adhesion, mechanical stability was evaluated through tensile strength tests and atomic force microscopy (AFM). Results: The study demonstrated that vitamin D nanoparticle treatment significantly enhanced cellular viability, resulting in a 30% increase in osteoblastic cell proliferation. Alizarin Red staining indicated a marked increase in calcium deposits on vitamin D-treated surfaces. At the same time, gene expression analysis revealed a 40% increase in alkaline phosphatase (ALP) and a 35% increase in osteocalcin. Additionally, AFM results showed improved cell adhesion on treated surfaces, correlating with increased tensile strength during mechanical testing. Discussion: Vitamin D nanoparticles significantly improve osseointegration in osteoporotic patients by enhancing cell adhesion, viability, and differentiation. The treated surfaces exhibited better organization and mineralization, improving bone regeneration. This innovative approach addresses the challenges of low bone density and compromised osseointegration in such patients. Conclusion: The application of vitamin D nanoparticles on titanium implant surfaces represents a promising advancement in dental implantology, particularly for osteoporotic patients. Further studies are warranted to optimize therapeutic protocols and investigate the long-term clinical implications of this innovative treatment.